2011
DOI: 10.1051/epjap/2011110055
|View full text |Cite
|
Sign up to set email alerts
|

UV irradiation influence on the structural and optical properties of CdO thin films

Abstract: Polycrystalline Cd thin films were evaporated in a vacuum onto glass substrates at Cd source temperature of 770 K. The as-deposited Cd films were subjected to a gradual heating at the rate of 5 K/min, up to a temperature of 650 K and were then maintained at this temperature for 5 min. Then, the respective samples were cooled down to room temperature at the same rate. The obtained CdO thin films were UV irradiated for 2h (150W mercury lamp, 3.18-3.65 eV). By means of XRD, AFM and XPS techniques, the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Some recent studies [10][11][12][13][14][15][16][17][18] showed the effects of irradiation on the optical and structural CdO thin films properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies [10][11][12][13][14][15][16][17][18] showed the effects of irradiation on the optical and structural CdO thin films properties.…”
Section: Introductionmentioning
confidence: 99%
“…A wave propagating in z direction with a frequency (ʋ), can be described by [27]: Note that the last term is damping factor. The fraction of incident power is available after propagation a distance z through a material =e (-4πʋkz/c) …………………………………………………………………...…………………….….… (17).…”
Section: 5: Extinction Factor Determinationmentioning
confidence: 99%
“…Some recent studies [10][11][12][13][14][15][16][17][18] showed the effects of irradiation on the optical and structural CdO thin films properties.…”
mentioning
confidence: 99%